(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
In our society today, exchange of goods and services usually involves exchange of currency notes by hand. This can serve as a means of transferring microorganisms and antibiotics resistant bacterial isolates. This study was aimed at assessing the contamination of Naira notes in Ungwan Rimi area of Kaduna State and to determine the antibiotics resistance patterns of the isolated bacteria. A total of 160 samples of naira notes, were collected randomly from staff and students, marketers, hospital and pharmacies, food vendors and transporters at strategic spots in Ungwan Rimi. Bacteria isolation and identification of samples were carried out using spread plate technique on medium and standard biochemical characterization, respectively. Antibiotics susceptibility testing were carried out using agar disc diffusion method. Isolates that were non-susceptible to at least one antimicrobial agent in three or more antimicrobial classes were classified as multidrug resistant (MDR), those that remain susceptible to agent(s) in only one or two classes as extended drug resistant (XDR) while pandrug resistant (PDR) isolates were classified as those isolates that were resistant to all antibiotics used. Highest bacterial load was observed with N100 notes with marketers (5.33 x 105) while the least bacterial load was 1.2 x 104 in N50 notes from hospitals and pharmacies. The following bacteria were isolated Staphylococcus aureus 70 (26.8%), Bacillus spp 60 (23.0%), Clostridium spp 31 (11.9%), Escherichia coli 30 (11.5%), Streptococcus species 25 (9.6%), Klebsiella spp 24 (9.2%), Salmonella 15 (5.8%), Shigella species 4 (1.5%) and Pseudomonas species 2 (0.8%)...